The internet gaming disorder and its associated factors among college students at Imam Mohammed Ibn Saud Islamic University, Riyadh, Saudi Arabia: A cross-sectional study - Khalid Bin Abdulrahman; Tariq Y. Alhomoud; Ismail S. Alateeq; Faisal N. Al-Mohaisen; Musab S. Alshamrani; Saleh I. Alhathlul; Mohammed Abdulaziz Khamsah (Journal of Family Medicine and Primary Care)
Background: Internet gaming disorder (IGD) or video gaming has been considered by World Health Organization (WHO) and American Psychiatric Association (APA) as a disease. WHO defines IGD as a disease with a pattern of uncontrollable gaming behavior, characterized by increasing priority given to gaming over other activities to the point that gaming takes precedence over most interests and activities of daily living. Objectives: This research aims to estimate the prevalence and examine the association of IGD scores with gender, age, sleeping hours, academic performance, and occurrence of arguing with others post-gaming among college students. Methods: A cross-sectional study was conducted in October 2022 at (IMSIU), Riyadh, Saudi Arabia. A total of 1005 college students filled out an online self-administered questionnaire developed based on an extensive literature review and pilot study. Results: More than two-thirds (76.1%) of students are active gamers. The majority (65.8%) reported no effects of gaming on daily activities. yet, one-third considered games as the most daily time-consuming activity. The majority are playing games to relieve stress. Interestingly, male and senior students had the highest IGD scores (P = 0.017, P = 0.072, respectively). Unfortunately, there were associations between high IGD scores and having fewer sleeping hours as well as low academic performance (P = 0.046, P = 0.047, respectively). Negative social effects include arguing after gaming was significantly linked with higher IGD scores (P < 0.001). Conclusion: IGD was prevalent among college students. There was no impact of games on students’ daily activities; however, gaming was the most time-consuming part of daily activity for the remaining students. Most college students were playing games to feel better. Higher IGD score was associated with male, senior students, less sleeping hours, poor academic performance, and post-gaming arguments with others.